The relationship between physical environment comfort and quality of work life among supporting staff at Pangkalan Tentera Udara Diraja Malaysia Subang, Selangor Darul Ehsan / Nurul Alilah Azahari - Azahari, Nurul Alilah (Faculty of Business and Management, 2018)
The purpose of this study is to examine the relationship between physical environment comfort and quality of work life among supporting staff at Pangkalan Tentera Udara Diraja Malaysia Subang, Selangor darul Ehsan. The objective of this study is to examine the relationship between physical environments comforts with quality of work life and To determine which of the three physical environment factors namely air conditioning, lighting and noise, has the most influence on quality of work life among supporting at Pangkalan Tentera Udara Diraja Malaysia Subang, Selangor Darul Ehsan. 70 questionnaires were distributed among the supporting staff to achieve the objectives of th is study. The questionaires were distributed to the respondent ampong workers in three departments at Pangkalan Tentera Udara Diraja Malaysia Subang, Selangor Darul Ehsan. The data collected were analysed by using SPSS program. The findings in this study show about three independent variable which are air-conditioning, noise and lighting. There also dependent variable which is quality of work life. Lighting were the most influence towards quality of work life among supporting staff at Pangkalan Tentera Udara Diraja Malaysia Subang, Selangor Darul Ehsan. The result found that all variables are reliable and have significant relationship between air-conditioning, noise, and lighting with quality of work life